Yolk−shell Prussian blue analogues hierarchical microboxes: Controllably exposing active sites toward enhanced cathode performance for lithium ion batteries. (1st October 2019) - Ye, Wenjin; Yu, Lin; Sun, Ming; Cheng, Gao; Fu, Shuchai; Peng, Shaomin; Han, Shengbo; Yang, Xiaobo
Abstract: Due to the unique three-dimensional open framework with large interstitial sites, Prussian blue analogues offer great advantages in energy storage, however, besides solid cubic or hollow structure obtained by post treatments of etching or annealing, the fine structure of Prussian blue analogues remains difficult to control by one-step method. This may somewhat hinder its full application in energy storage. Herein, for the first time, a yolk-shell K0.86 Mn[Fe(CN)6 ]0.74 ·2.35H2 O microboxes with self-assembled hierarchical subunits are synthesized through a facile one-step approach. This growth process utilizes the self-assembly driving force of poly-vinyl pyrrolidone (PVP) to motivate the consumption of the interior bulky crystal to outward rearrangement, and meanwhile preserving the outer shell. By virtue of the flexible reaction time, controllable structures with specific surface area and pore size can be realized. As a cathode for lithium ion battery it exhibits a high specific capacity of over 160 mAh g −1 and excellent rate performance, owing to the tailored high specific surface area yolk-shell structures. The nano-structured shell and the porous voids provide large active surface to build up the electrolyte/electrode interface and enable fast kinetics for reversible Li + insertion and removal. With the help of highly reversible phase transition and sufficient expansion space for discharge/charge, the cathodes show an impressive cycling lifespan of 500 with over 80% capacity retention. This work highlights new insights into the rational design of Prussian blue analogues for rechargeable batteries. Graphical abstract: Image 1